2015
DOI: 10.1002/nme.5008
|View full text |Cite
|
Sign up to set email alerts
|

Computational homogenization of elasticity on a staggered grid

Abstract: In this article, we propose to discretize the problem of linear elastic homogenization by finite differences on a staggered grid and introduce fast and robust solvers. Our method shares some properties with the FFT-based homogenization technique of Moulinec and Suquet, which has received widespread attention recently because of its robustness and computational speed. These similarities include the use of FFT and the resulting performing solvers. The staggered grid discretization, however, offers three crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
189
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 179 publications
(200 citation statements)
references
References 79 publications
(159 reference statements)
6
189
0
Order By: Relevance
“…Methods based on Fast-Fourier Transforms (FFT) as introduced in [51] use a direct, point-wise discretization of the Lippmann-Schwinger equation, with improvements in [46] and [58]. In an effort to reduce the computation time by a modified modeling [60] introduce into FE 2 the rationale of a statistically similar representative volume element (SSRVE) in order to replace the true microstructure in its full geometrical complexity by a surrogate, which resembles the original one by geometrical features as analyzed by different geometrical similarity measures.…”
Section: Numerical Costsmentioning
confidence: 99%
“…Methods based on Fast-Fourier Transforms (FFT) as introduced in [51] use a direct, point-wise discretization of the Lippmann-Schwinger equation, with improvements in [46] and [58]. In an effort to reduce the computation time by a modified modeling [60] introduce into FE 2 the rationale of a statistically similar representative volume element (SSRVE) in order to replace the true microstructure in its full geometrical complexity by a surrogate, which resembles the original one by geometrical features as analyzed by different geometrical similarity measures.…”
Section: Numerical Costsmentioning
confidence: 99%
“…defined on a trial space V = ∇H The Fourier-Galerkin method, described for homogenisation in [1][2][3][4][5], belongs to FFT-based methods introduced in [6] and investigated and developed to many different schemes such as [7][8][9]. is based on Galerkin approximation with trigonometric polynomials of uniform order N = (n, .…”
Section: Application To Numerical Homogenisation Within Fourier-galermentioning
confidence: 99%
“…First-order finite difference-based approximations composed onto Fourier transforms have been shown to result in significantly mitigating oscillatory artifacts (Müller, 1996;Brown et al, 2002;Berbenni et al, 2014;Brisard and Dormieux, 2010;Lebensohn and Needleman, 2016;Schneider et al, 2016), while maintaining consistency with the original governing equations with h-refinement. Willot et al (2014) showed that rotated first-order schemes show a marked reduction in oscillatory artifacts.…”
Section: Introductionmentioning
confidence: 99%